Pre-miRNA loop nucleotides control the distinct activities of mir-181a-1 and mir-181c in early T cell development. - Gwen Liu; Hyeyoung Min; Sibiao Yue; Chang-Zheng Chen (PLoS ONE)
Background Mature miRNAs can often be classified into large families, consisting of members with identical seeds (nucleotides 2 through 7 of the mature miRNAs) and highly homologous approximately 21-nucleotide (nt) mature miRNA sequences. However, it is unclear whether members of a miRNA gene family, which encode identical or nearly identical mature miRNAs, are functionally interchangeable in vivo. Methods and findings We show that mir-181a-1, but not mir-181c, can promote CD4 and CD8 double-positive (DP) T cell development when ectopically expressed in thymic progenitor cells. The distinct activities of mir-181a-1 and mir-181c are largely determined by their unique pre-miRNA loop nucleotides-not by the one-nucleotide difference in their mature miRNA sequences. Moreover, the activity of mir-181a-1 on DP cell development can be quantitatively influenced by nucleotide changes in its pre-miRNA loop region. We find that both the strength and the functional specificity of miRNA genes can be controlled by the pre-miRNA loop nucleotides. Intriguingly, we note that mutations in the pre-miRNA loop regions affect pre-miRNA and mature miRNA processing, but find no consistent correlation between the effects of pre-miRNA loop mutations on the levels of mature miRNAs and the activities of the mir-181a-1/c genes. Conclusions These results demonstrate that pre-miRNA loop nucleotides play a critical role in controlling the activity of miRNA genes and that members of the same miRNA gene families could have evolved to achieve different activities via alterations in their pre-miRNA loop sequences, while maintaining identical or nearly identical mature miRNA sequences.